2015
DOI: 10.1039/c4cy01237b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of glycerol carbonate by direct carbonylation of glycerol with CO2 over solid catalysts derived from Zn/Al/La and Zn/Al/La/M (M = Li, Mg and Zr) hydrotalcites

Abstract: Zn/Al/La and Zn/Al/La/M (M = Li, Mg, Zr) mixed oxides were obtained by calcination of hydrotalcites and tested for glycerol carbonate synthesis from CO2 carbonylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 60 publications
(114 reference statements)
3
54
0
Order By: Relevance
“…With regard to the carbonylation of glycerol and CO 2 , Zhao and co-workers reported that Zn/Al/La/M (M = Li, Mg, Zr) hydrotalcite-like catalysts and halogen anions (F − , Cl − and Br − ) modified Zn/Al/La (Zn/Al/La = 4:1:1) mixed oxides. 47,48 Under optimal reaction conditions, the yield of GC was 18.7% and 16.0% in the two corresponding works. The introduction of Li, Mg, and Zr improved the catalytic activity due to the increased amount of weak basic sites, which favored both CO 2 activation and CH 3 CN hydrolysis.…”
Section: Synthesis Of Glycerol Carbonates From Glycerol and Comentioning
confidence: 88%
See 3 more Smart Citations
“…With regard to the carbonylation of glycerol and CO 2 , Zhao and co-workers reported that Zn/Al/La/M (M = Li, Mg, Zr) hydrotalcite-like catalysts and halogen anions (F − , Cl − and Br − ) modified Zn/Al/La (Zn/Al/La = 4:1:1) mixed oxides. 47,48 Under optimal reaction conditions, the yield of GC was 18.7% and 16.0% in the two corresponding works. The introduction of Li, Mg, and Zr improved the catalytic activity due to the increased amount of weak basic sites, which favored both CO 2 activation and CH 3 CN hydrolysis.…”
Section: Synthesis Of Glycerol Carbonates From Glycerol and Comentioning
confidence: 88%
“…The introduction of Li, Mg, and Zr improved the catalytic activity due to the increased amount of weak basic sites, which favored both CO 2 activation and CH 3 CN hydrolysis. 47 By reconstructing Zn/Al/La mixed oxides with halogen anions, the specific surface area and the binding energies of Zn 2p 3/2 of hydrocalcites were found to increase, but the basicity decreased. The introduction of Cl − and Br − anions promoted the reaction, and better performance was obtained with the addition of Cl − (Table 5).…”
Section: Synthesis Of Glycerol Carbonates From Glycerol and Comentioning
confidence: 97%
See 2 more Smart Citations
“…Associating with the specific surface area of as-prepared catalysts, CeO 2 _NW_x (x > 500) catalysts with tinier surface area proof inferior catalytic activity, illustrating that the catalytic performance is directly related to the specific surface area of as-prepared catalysts. Smaller specific surface area necessarily leads to the covering of efficient active sites and causes lower catalytic activity [34,35].…”
Section: Catalytic Performancementioning
confidence: 99%